The Effectiveness of Intelligent Character Education- Group Format (ICE-GF) to Prevent Student Bullying Behavior - Diantifani Harlianda; Prayitno Prayitno; Mudjiran Mudjiran (Journal of Educational and Learning Studies, 2020)
The phenomenon of bullying in Indonesia is very worrying for the development of teenagers’ life. This study used a quantitative approach with an experimental method. The design used was a pre-experimental one group pretest-posttest design. The data were collected from 33 students as the sample of this study taken by using a purposive sampling technique. The experimental group was divided into 3 groups, namely group A, group B and group C. Each group consisted of 11 members. The data were collected by using a questionnaire students’ BMB3 conditions about bullying (55 valid items = 0.889). Data were analyzed by using the Wilcoxon signed rank test with the help of SPSS version 20.00 to measure the differences between two paired groups on ordinal data. The findings of the study showed that intelligent character education-group format was effective for improving the conditions about thinking, feeling, behaving, acting, and being responsible for the students against bullying so it can prevent bullying behavior.